Preserving Local Wisdom and Cultivating Global Values: An Etnopedagogical Approach to Islamic Religious Education in Jambi's Public Higher Education - K.A. Rahman; Kemas Abdul Hai; Anwar Sanusi; Neldi Harianto; Helmun Jamil (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The purpose of this study is to explore how Jambi's local wisdom values ​​are instilled in Islamic Religious Education (IRE) learning at higher education through an ethnopedagogical approach. Using a qualitative approach with a phenomenological design, this study examines the experiences of eight IRE lecturers in instilling local values ​​at each stage of the lecture. The results show that each lecturer brings a unique nuance to their learning practices: L1 instills the value of religious togetherness through communal prayer, group work, and tion; L1 makes the value of customary deliberation as both a method and material; L3 emphasizes the value of cooperation through collaborative projects; L4 instills the value of politeness and etiquette through Jambi Malay pantun; L5 prioritizes the value of honesty and justice through moral contracts; L6 instills ecological values ​​with Islamic ecotheology; L7 instills the value of hard work through academic challenges; and L8 instills the value of tolerance through the practice of cross-perspective dialogue. These findings demonstrate that ethnopedagogy can provide a learning space that not only transfers knowledge but also fosters local identity as well as universal values. The implication of this research is the importance of developing an IRE learning model based on local wisdom values ​​that are in line with global values, so that higher education is not uprooted from the cultural roots of society and can answer the challenges of globalization